Study the Effect of Forming Media on the Hydroforming Process for Copper Tube - Salman, Rusul AbdulKareem; Ameen, Hani Aziz; Mashloosh, Kadhim Mijbel (Al-Khwarizmi Engineering Journal, 2018)
To observe the effect of media of the internal pressure on the equivalent stress distribution in the tube, an experimental study is done by constructing a testing rig to apply the hydraulic pressure and three dies are manufactured with different bulging configurations (square, cosine, and conical). In the other part, ANSYS APDL is generated to analyze the bulging process with hydraulic and rubber (natural and industrial) media. It was found that when the media is a rubber, the stress is decreased about 9.068% in case of cosine die and 5.4439% in case of conical die and 2.8544% in case of square die. So, it can be concluded that the internal pressure in the rubber media is much better than in hydraulic media. Also, the force needed for forming the shape using rubber is higher than that of hydraulic and the force needed to form using industrial rubber is higher than of natural rubber. The thickness distribution in the tube wall in case of rubber media is better than that for hydraulic media and for the industrial rubber is better than that for natural rubber for the same dies. In case of hydraulic, the lower forming pressure is needed to bulging process compared with the rubber media since height stress in the tube metal is existed, which causes the failure. For the case of rubber, the forming pressure that was needed to bulge process is higher when compared with the hydraulic media but with less stress in tube metal and the failure in the wall is not existed with rubber media for the same pressure of hydraulic.